NUSYUZ IN FIQH AND MODERN PRACTICE: A CROSS-SCHOOL DOCTRINAL ANALYSIS AND CONTEMPORARY CONTEXTUALIZATION - Azhar Nur Mawaddah Gulo; Heri Firmansyah (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2026)
Ideally, marriage should create a harmonious family, but household dynamics are often threatened by the threat of rift caused by the phenomenon of nusyuz. Nusyuz is often biasedly identified as a wife's disobedience, even though this attitude can occur reciprocally between partners when they neglect their obligations. The research aims to explain the idea of nusyuz from the perspective of various Islamic schools of jurisprudence and to analyze its adaptation and contextualization in modern practice. Methods The type of library research used is qualitative, normative-theoretical in nature through a comparative approach between schools of jurisprudence. The results of the study indicate differences in the definition of nusyuz and its implications for the right to maintenance among jurists. The Hanafi, Maliki, and Shafi'i schools agree that a wife's right to maintenance is forfeited if she leaves the residence without permission (khuruj), but if the wife refuses intimate relations but lives with her husband (ihtibas), she still has the right to maintenance according to the well-known opinion of the three schools of jurisprudence. In the modern era, physical resolution measures (beating) in QS. An-Nisa: 34 faces legal challenges due to its conflict with Human Rights standards and the Law to End Domestic Violence (UU PKDRT). In conclusion, modern practice deconstructs classical understanding by prioritizing the principle of equal partnership (mubadalah). Nusyuz is now interpreted as a disregard for shared commitments, where refusal of intimate relations for health or psychological reasons is no longer considered disobedience. Conflict resolution is more directed towards psychological approaches, mediation by peacemakers (hakam), and peace (ishlah), while physical action is strictly avoided to uphold humanitarian values.